2016
DOI: 10.1128/jvi.00619-16
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus-Induced Upregulation of MicroRNA miR-146a-5p in Hepatocytes Promotes Viral Infection and Deregulates Metabolic Pathways Associated with Liver Disease Pathogenesis

Abstract: Hepatitis C virus (HCV)-induced chronic liver disease is a leading cause of hepatocellular carcinoma (HCC). However, the molecular mechanisms underlying HCC development following chronic HCV infection remain poorly understood. MicroRNAs (miRNAs) play an important role in homeostasis within the liver, and deregulation of miRNAs has been associated with liver disease, including HCC. While host miRNAs are essential for HCV replication, viral infection in turn appears to induce alterations of intrahepatic miRNA ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 75 publications
6
70
0
Order By: Relevance
“…Other miRNAs, including miR-155, miR-146a-5p, miR-135a-5p and miR-373, were shown to either promote or inhibit HCV-associated hepatocarcinogenesis. (45)(46)(47)(48) Our study highlighted how intratumoral introduction of synthetic miR-181c inhibits tumor progression in a HCC xenograft tumor model. Recent introduction of direct-acting antivirals (DAAs) with the combinations of virus replication inhibitors may achieve a decrease in virus titer to a sustained virological response in HCV-infected patients.…”
Section: Discussionmentioning
confidence: 88%
“…Other miRNAs, including miR-155, miR-146a-5p, miR-135a-5p and miR-373, were shown to either promote or inhibit HCV-associated hepatocarcinogenesis. (45)(46)(47)(48) Our study highlighted how intratumoral introduction of synthetic miR-181c inhibits tumor progression in a HCC xenograft tumor model. Recent introduction of direct-acting antivirals (DAAs) with the combinations of virus replication inhibitors may achieve a decrease in virus titer to a sustained virological response in HCV-infected patients.…”
Section: Discussionmentioning
confidence: 88%
“…In a 2016 article, the authors observed an upregulation of miR-146a in HCV-infected hepatocytes and liver tissue from patients suffering from HCV. They also provided evidence for miR-146a's involvement in HCV replication, where the miRNA supported HCV infection of cells (Bandiera et al, 2016). Again, this concept needs to be explored further before any solid conclusions can be made.…”
Section: Hepatocellular Carcinomamentioning
confidence: 98%
“…Previous evidence has suggested that there is a complex association between miRNAs and HBV genes (29)(30)(31). The mechanism of HBV infection in regulating miRNAs may be through either RNA interference or the inhibition of translational initiation and elongation (23,(32)(33)(34). In addition, deregulated expression of miRNAs may be present for a long period prior to the onset of disease (35).…”
Section: Discussionmentioning
confidence: 99%